Assessing the Factors Influencing Consumer Behaviour in E-Commerce Platforms - Yong, Sean Calvin Shin Ching; Huan, Rui Tian; Poh, Wen Sern; Osman, Muzaini; Ng, Dany Chi Wai (Future Science / FSH-PH Publications, 2023)
This paper examined the various factors proposed in the literature that have potential to impact consumer behaviour within the context of e-commerce platforms. The field of consumer behaviour involves the analysis of the actions and reactions of individual consumers in response to business practises. This is particularly pertinent within the realm of e-commerce and online retail, as they differentiate themselves from traditional commerce by virtue of their unique functionalities and characteristics. It is worth noting that e-commerce has the ability to distinctly impact consumer behaviour. By employing questionnaire surveys to gather data and evidence, followed by conducting various forms of analysis such as descriptive and inferential analysis, we have ascertained that consumer behaviour can be positively influenced by factors such as sales and promotion, a favourable reputation of the e-commerce retailer, and a satisfactory user experience. This study has effectively identified the distinctive factors that empower e-commerce retailers to exert influence over consumer behaviour. It is suggested that these findings possess the potential to contribute significantly to the current body of knowledge on e-commerce retailing.